COping strategies by stroke caregivers: Evidence from a qualitative study In Sarawak, Malaysia - Rahman M.M.; Putit Z.B.; Suut N.B.; Arif M.T.; Bin Said A.; Bin Suhaili M.R.; Fadzillah M.; Tambi Z.B.; Kee L.H. (Malaysian Public Health Physicians Association, 2024)
Indexed by Scopus/MyCite